2014
DOI: 10.1002/ajmg.a.36453
|View full text |Cite
|
Sign up to set email alerts
|

Genetic counselor review of genetic test orders in a reference laboratory reduces unnecessary testing

Abstract: Genetic tests are routinely ordered by health care providers (HCPs) within a wide range of medical specialties. Many providers have limited knowledge or experience with ordering and interpreting genetic tests; thus, test order errors are common. Rigorous review of genetic test orders by genetic counselors (GCs) can provide a direct financial benefit to medical institutions, patients and insurers. GCs at ARUP (Associated Regional University Pathologists) Laboratories routinely perform a preanalytic assessment o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
76
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(78 citation statements)
references
References 6 publications
1
76
0
1
Order By: Relevance
“…Inclusion of genetic counselors can improve access to and elevate the quality of patient care 10,36 and reduce the cost of medical expenses. 37 Our study identified several opportunities for growth in a time of crucial need for genetic workforce expansion. Two strategies were highlighted because of the systemic impact they would have on multiple barriers: reevaluation of the current GC education model and increased funding for GC education and genetic services.…”
Section: Discussionmentioning
confidence: 92%
“…Inclusion of genetic counselors can improve access to and elevate the quality of patient care 10,36 and reduce the cost of medical expenses. 37 Our study identified several opportunities for growth in a time of crucial need for genetic workforce expansion. Two strategies were highlighted because of the systemic impact they would have on multiple barriers: reevaluation of the current GC education model and increased funding for GC education and genetic services.…”
Section: Discussionmentioning
confidence: 92%
“…Genetic testing for adult-onset conditions in children should not be undertaken without medical and/or psychosocial justification and a discussion with family members, although pathogenic variants in adult-onset cancer genes may be revealed by large panels, tumor-based testing, or whole exome/genome analysis as an incidental finding (20). Genetic testing without genetic counseling has been linked with a variety of negative testing outcomes including a lack of informed decision making around testing; ordering of costly, unnecessary genetic testing; misinterpretation of genetic test results; inappropriate or inadequate medical management; violations of ethical standards; and adverse psychosocial outcomes (21)(22)(23). The informed consent process should include a discussion about the implications of the results to the patient (including discussion of the surveillance protocol, or lack thereof, for the child if found to have a hereditary cancer predisposition syndrome), psychosocial and ethical considerations, confidentiality and privacy concerns (which varies with the laws of different countries), the implications of the results for other relatives, logistics including a plan for disclosing results, and the option of deferring or declining testing (15,(24)(25)(26).…”
Section: Pretest Genetic Counseling and Informed Consentmentioning
confidence: 99%
“…Genetic testing performed without pre-and posttest genetic counseling by qualified clinicians has been associated with negative patient and societal outcomes such as misinterpretation of genetic test results, inappropriate medical management, lack of informed decision making, violation of established ethical standards, adverse psychosocial outcomes, and costly, unnecessary genetic testing. [1][2][3] Cancer genetic consultation is an important aspect of the care of individuals at increased risk of a hereditary cancer syndrome. [4][5][6][7][8] Yet, several patient, clinician, and system-level barriers hinder the identification of individuals appropriate for cancer genetics referral.…”
mentioning
confidence: 99%